Sector-Specific and Spatial-Specific Multipliers in Indonesian Economy: World Input-Output Analysis - Muchdie, Muchdie; Nurrasyidin, M (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2018)
This article discusses on sectoral-specific and spatial-specific multipliers in Indonesian economy using 6-country-30 sector input-output tables for the year 2000, 2005, 2010 and 2014. The result shows that firstly, in all years, there were 20 sectors with total output multipliers more than 2. Flow-on effects were higher than initial effects. These sectors should be prioritized if increasing of total output is the objective of Indonesian economic development as total output will be created with less intial efforts.Â  Secondly, in the year of 2000, average percentage of multipliers occurred in own-sector was 56.23 per cent, and increase slightly in 2005 (57.38%) dan 2010 (58.93%), but decrease in 2014 (57.98%). Correlation between total output multipliers and percentage of multipliers occurred in other-sector was positive and very strong. The higher total output multipliers, the higher percentage of multipliers occurred in other-sector. Thirdly, in the year of 2000, average percentage of multipliers occurred in other-countries was 21.34 per cent and decrease slightly in 2005 (20.22%) and 2010 (18.14%), but increase in 2014 (20.55%). Correlation between total output multipliers and percentage of multipliers occurred in other-countries were positive and very strong. The higher total output multipliers, the higher multipliers occurred in other-countries.Â